2011
DOI: 10.1029/2010ja016372
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of magnetosonic waves in the terrestrial magnetosphere: Particle-in-cell simulations

Abstract: [1] Two-dimensional electromagnetic particle-in-cell simulations are performed to study the temporal development of an ion Bernstein instability driven by a proton velocity distribution with positive slope in the perpendicular velocity distribution f p (v ? ), where ? denotes directions perpendicular to the background magnetic field B 0 . A subtracted Maxwellian distribution is first used to construct the positive slope in f p (v ? ), and linear kinetic dispersion analysis is performed. The results of a simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
152
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(159 citation statements)
references
References 33 publications
7
152
0
Order By: Relevance
“…Furthermore, the ion shell distribution was used, with finite thermal spread and a cold ion background. The results of the simulations conducted by Lui et al 22 resembled the observed fast magnetosonic waves found in different regions of the magnetosphere, consistent with their theoretical model.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the ion shell distribution was used, with finite thermal spread and a cold ion background. The results of the simulations conducted by Lui et al 22 resembled the observed fast magnetosonic waves found in different regions of the magnetosphere, consistent with their theoretical model.…”
supporting
confidence: 82%
“…Their work was motivated by observations in the terrestrial magnetosphere, near the plasma sheet boundary layer, of enhanced field fluctuation spectra, 21 believed to be produced by ion Bernstein waves. Lui et al 22 performed fully electromagnetic particlein-cell simulations to study the temporal development of an ion Bernstein instability driven by a proton velocity distribution, with a positive slope in the perpendicular velocity distribution. The subtracted Maxwellian distribution was first used to produce the positive slope, in accordance with earlier work by Gary et al, 10 to compare simulation results with those from the kinetic theory.…”
mentioning
confidence: 99%
“…The time evolution of the mean square pitch angle change, <Δ α 2 >, of the test electrons is then calculated and the time derivative of <Δ α 2 > during its linear growth phase is used to determine the pitch angle diffusion coefficient. The test particle approach studies electron scattering at a fundamental level and can well reproduce the quasi‐linear diffusion coefficients for EMIC waves [ Liu et al , 2010a, 2010b], whistler waves [ Tao et al , 2011], and fast magnetosonic waves [ Liu et al , 2011], at sufficiently small wave amplitudes. As fluctuation amplitudes increase, this approach provides clear criteria as to when quasi‐linear theory no longer provides a valid approximation for the diffusion coefficients [ Liu et al , 2010a].…”
Section: Effects Of Phase Trapping and Bunching On Diffusion Coefficimentioning
confidence: 99%
“…Both observations [Meredith et al, 2008] and simulations [Chen et al, 2010;Liu et al, 2011;Ma et al, 2014] have shown that such equatorial MS waves are preferentially excited by proton ring distributions. The signatures of MS waves include their low ellipticity, which leads to nearly linear polarization, and their nearly perpendicular propagation, which results in much stronger E ⟂ and B ∥ components compared to E ∥ and B ⟂ components, respectively .…”
Section: Introductionmentioning
confidence: 99%